2014
DOI: 10.1039/c3nr04759h
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-analogue carbon nitride: novel exfoliation synthesis and its application in photocatalysis and photoelectrochemical selective detection of trace amount of Cu2+

Abstract: Graphene-analogue nanostructures defined as a new kind of promising materials with unique electronic, surface and optical properties have received much attention in the fields of catalysis, energy storage, sensing and electronic devices. Due to the distinctive structure characteristics of the graphene-analogue materials, they brought novel and amazing properties. Herein, graphene-analogue carbon nitride (GA-C₃N₄) was synthesized by high-yield, large-scale thermal exfoliation from the graphitic C₃N₄-based inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(204 citation statements)
references
References 43 publications
7
188
1
1
Order By: Relevance
“…Five layers of PTI-0 led to a bandgap of 4.4 eV, sufficient to represent that of the bulk material, confirming the influence of the packing to narrow the corresponding bandgap. 58 Figure 3 presents the band positions for the five-layer slab of PTI-0 and TAP-doped PTI monolayers. Using a monolayer configuration, the calculation revealed a bandgap reduction by 0.6 eV by PTI-0.143 with respect to PTI-0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five layers of PTI-0 led to a bandgap of 4.4 eV, sufficient to represent that of the bulk material, confirming the influence of the packing to narrow the corresponding bandgap. 58 Figure 3 presents the band positions for the five-layer slab of PTI-0 and TAP-doped PTI monolayers. Using a monolayer configuration, the calculation revealed a bandgap reduction by 0.6 eV by PTI-0.143 with respect to PTI-0.…”
Section: Resultsmentioning
confidence: 99%
“…The calculations revealed a 0.48 eV increase in bandgap upon exfoliation to the monolayer, consistent with the trend of the measured values. 58 Following a single point calculation on one non-optimized layer in the bulk structure, it was determined that this effect is almost entirely electronic and unrelated to the relaxation of the atomic positions. Five layers of PTI-0 led to a bandgap of 4.4 eV, sufficient to represent that of the bulk material, confirming the influence of the packing to narrow the corresponding bandgap.…”
Section: Resultsmentioning
confidence: 99%
“…19 Although the characteristic absorption peaks of free CRL were highly overlapped with the absorption peaks of C 3 N 4 -NS, peaks could also be revealed due to CRL and C 3 N 4 -NS in the curve of C 3 N 4 -NS@CRL. These results suggest that the whole immobilization process could make sure that the basic structure of carbon nitride nanosheets was intact.…”
Section: View Article Onlinementioning
confidence: 97%
“…Meanwhile, the later dominant peak (2q ¼ 27 ) originated from the (002) interlayer diffraction of graphitelike layered structures. 19 The slight weakening of the characteristic peaks of C 3 N 4 -NS compared to the C 3 N 4 samples suggested that the interlayer stacking pattern of C 3 N 4 and the planar size of C 3 N 4 layers were weakened during the exfoliation process. Meanwhile, the characteristic diffraction angles of glutaraldehyde-modied C 3 N 4 -NS (G-C 3 N 4 -NS) and C 3 N 4 -NS@CRL exhibited no obvious difference to C 3 N 4 -NS, indicating that C 3 N 4 -NS retained its specic crystal texture and could ensure the mass transfer on the surface of C 3 N 4 -NS@CRL during catalytic reactions.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation